Guts & glory : the American Civil War - Thompson, Ben, 1980-; Butzer, C. M. (New York : Little, Brown and Company, 2014)
Presents funny and unbelievable, but true, events from the Civil War.
First blood -- A clash of ironclads -- Shiloh -- The Cleopatra of the secession -- The great locomotive chase -- Robert E. Lee in Northern Virginia -- The deadliest day -- Chancellorsville -- Horse and steel -- Gettysburg -- The making of the Confederate navy -- The 54th Massachusetts -- Morgan's Raid -- The Confederate Thermopylae -- The Rock of Chickamauga -- Mary Edwards Walker, Union nurse -- Grant versus Lee -- Mobile Bay -- The presidential election of 1864 -- The end of the line.
Includes bibliographical references (pages 301-308) and index.
Booklist
Publishers Weekly
School Library Journal
Kirkus Reviews
8-12.
Keywords: United States -- History -- 1861-1865, Civil War; United States -- History -- 1861-1865, Civil War -- Campaigns